2020
DOI: 10.1101/2020.04.27.20082503
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Latent Blowout of COVID-19 Globally: An Effort to Healthcare Alertness via Medical GIS Approach

Abstract: Since January 2020, the COVID-19 pandemic has been escalating from North America to Asia. Various studies projected the spread of pandemic globally, using air passenger data from an infected area. But there could be various parameters that can be the basis for the forecasting of the pandemic. Current research adopts the Medical GIS approach and incorporates critical parameters from various domains to create a global alertness scale to combat the pandemic. The finding of the study ranks the countries on a 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The first symptoms of COVID-19 in Iran (Qom Province that imported from Wuhan, China) were observed on February 19, 2020. Some research mentioned Iran as one of the most affected countries, globally, almost among the first fifth countries (e.g., Sharma and Verma 2020;Binti Hamzah et al 2020). As Shojaee et al (2020) reported that the countries with the highest number of confirmed cases and deaths after China are Italy, Iran, and South Korea.…”
Section: Case Studymentioning
confidence: 99%
“…The first symptoms of COVID-19 in Iran (Qom Province that imported from Wuhan, China) were observed on February 19, 2020. Some research mentioned Iran as one of the most affected countries, globally, almost among the first fifth countries (e.g., Sharma and Verma 2020;Binti Hamzah et al 2020). As Shojaee et al (2020) reported that the countries with the highest number of confirmed cases and deaths after China are Italy, Iran, and South Korea.…”
Section: Case Studymentioning
confidence: 99%
“…The present paper examines Iran as the second-largest country in the Middle East (Fig. 1 ), the area of this country is 1873959 and it has an arid and semi-arid climate [ 32 ]. Iran has 31 provinces due to its political characteristics according to several studies, Iran has suffered the most harm from the virus in the world and ranks fifth in terms of vulnerability [ 33 ].…”
Section: Methodsmentioning
confidence: 99%